GAME OF PAPERS OR PROTAGONIZED GAME IN THE ORGANIZATION OF EDUCATION IN CHILDREN EDUCATION - Duarte, Rita de Cassia [UNESP]; Derisso, Jose Luis [UNESP]; Melo Duarte, Elaine Cristina; Duarte, Newton [UNESP] (Unesp-faculdade Ciencias & Letras, 2017)
This paper approaches issues about stages of mental development based on the work of Daniil El'konin and the theoretical methodological foundations of historical cultural psychology in L. S. Vygotsky and A. N. Leont'ev. It is analyzed the mental development as part of the development of personality in the context of childhood school education from the perspective of historical critical pedagogy of Dermeval Saviani.
Keywords: Childhood education; cultural historical psychology; historical critica pedagogy